MiR-181a-5p inhibits goose granulosa cell viability by targeting SIRT1. Issue 3 (4th May 2021) - Rong, Y.; Mo, Y.; Liu, Y.; Deng, Y.; Hu, S.; Li, L.; Hu, J.; Hu, B.; He, H.; Wang, J.
ABSTRACT: 1. Granulosa cells (GCs) are involved in folliculogenesis, follicular development, and atresia. Previous studies have shown that microRNA-181a-5p (miR-181a-5p) and sirtuin 1 ( SIRT1 ) are involved in GC proliferation and apoptosis, and SIRT1 has been predicted as one target of miR-181a-5p. However, there are few studies with poultry. 2. Quantitative real-time PCR (qRT-PCR) was used to detect the expression level of miR-181a-5p in granulosa layers during geese ovarian follicular development. A methyl thiazolyl tetrazolium (MTT) assay was performed to assess the viability of geese granulosa cells treated with miR-181a-5p mimic or inhibitor. The binding sites between the SIRT1 3′-UTR region and miR-181a-5p were evaluated using a luciferase reporter assay system. SIRT1 mRNA levels were detected using qRT-PCR after transfection with miR-181a-5p mimic and inhibitor. 3. The miR-181a-5p suppressed geese GC viability and regulated the mRNA expression of viability-related genes in geese GCs. SIRT1 was a target gene of miR-181a-5p and miR-181a-5p suppressed its mRNA expression. 4. The miR-181a-5p may target and inhibit SIRT1 expression, thus suppressing GC viability by regulating viability-related key genes.